William S. Burroughs and The Wild Boys Against the Language Virus: A Biosemiotic Guerilla - Patoine, Pierre-Louis (Recherches sémiotiques / Semiotic Inquiry, 2019)
This article proposes a biosemiotic reading of William S. Burroughs’ The Wild Boys– A Book of the Dead (1971), showing how literature, by cutting up narrative structures and syntactical units, can fight the language virus’ configuring of human vitality, just like bacteria uses CRISPR-Cas9 to cut-up the DNA code-chains of threatening viruses. We will see that, supported by the shared biosemiosic nature of literary texts and biological forms, this parallel extends beyond the metaphorical to reinsert literature within the realm of living processes.